New Role of Quinolones in Respiratory Tract Infections - Ronald F Grossman (Canadian Journal of Infectious Diseases)
Because of limited activity of the standard quinolones such as ciprofloxacin and ofloxacin against some clinically important organisms including Streptococcus pneumoniae and methicillin-resistant Staphylococcus aureus, new quinolones have been developed. In addition to their improved activity against S pneumoniae, some also demonstrate excellent anaerobic activity. None of the quinolones have a role to play in the treatment of paediatric infections. Quinolones (both older and newer agents) have demonstrated equivalent efficacy to standard antimicrobials in the treatment of acute sinusitis. Several groups have suggested that quinolones are excellent agents in the treatment of high risk patients with acute exacerbations of chronic bronchitis. These patients include the elderly, and those with frequent exacerbations, significant comorbid conditions. long duration of chronic bronchitis and major impairment of lung function. There is no evidence to suggest that the newer quinolones will differ from the currently available agents for th is disease. The major advantage of the newer quinolones appears to be in the treatment of patients with community-acquired pneumonia where pneumococcal infection is a real concern. A new parenteral quinolone with pneumococcal activity may replace the standard macrolide/cephalosporin combination that is commonly prescribed. For patients with nosocomial pneumonia, the newer agents are alternative choices, especially among patients with early onset pneumonia (less than five days of hospitalization), but are unlikely to replace ciprofloxacin in the intensive care unit setting because of poor Pseudomonas aeruginosa coverage.